2015
DOI: 10.1126/scisignal.aaa0354
|View full text |Cite
|
Sign up to set email alerts
|

WNK1-regulated inhibitory phosphorylation of the KCC2 cotransporter maintains the depolarizing action of GABA in immature neurons

Abstract: Activation of Cl(-)-permeable γ-aminobutyric acid type A (GABAA) receptors elicits synaptic inhibition in mature neurons but excitation in immature neurons. This developmental "switch" in the GABA function depends on a postnatal decrease in intraneuronal Cl(-) concentration mediated by KCC2, a Cl(-)-extruding K(+)-Cl(-) cotransporter. We showed that the serine-threonine kinase WNK1 [with no lysine (K)] forms a physical complex with KCC2 in the developing mouse brain. Dominant-negative mutation, genetic depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
225
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(243 citation statements)
references
References 71 publications
17
225
1
Order By: Relevance
“…Recently, WNK1-dependent inhibitory phosphorylation of KCC2 was shown to maintain the depolarizing action of GABA in the developing mouse brain (10). In immature neurons, WNK1 inhibition triggered a hyperpolarizing shift in GABA activity by reducing KCC2 Thr906/Thr1007 phosphorylation and enhancing KCC2-mediated Cl − extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, WNK1-dependent inhibitory phosphorylation of KCC2 was shown to maintain the depolarizing action of GABA in the developing mouse brain (10). In immature neurons, WNK1 inhibition triggered a hyperpolarizing shift in GABA activity by reducing KCC2 Thr906/Thr1007 phosphorylation and enhancing KCC2-mediated Cl − extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of a dominant-negative, kinase-dead WNK1 in immature neurons has a similar effect that is reversed by simultaneous knockdown of KCC2. These results were also recapitulated with chemical inhibition of WNK1 (Friedel et al, 2015) suggesting that WNK1 inhibition of KCC2 in immature neurons maintains a higher intracellular chloride concentration. Indeed, WNK1 inhibits the activity of all mammalian KCCs when co-expressed in Xenopus oocytes (Fig.…”
Section: Emerging Functions Of the Wnk Signaling Axis In Developmentmentioning
confidence: 59%
“…In cells in which KCC2 is inactivated by introducing phospho-mimicking threonine-to-glutamate mutations, WNK1 inhibition has no effect on intracellular chloride. Together, the results suggest that increased WNK1 activity in immature neurons maintains KCC in a phosphorylated, inactive state that allows for higher intracellular chloride at that developmental timepoint (Friedel et al, 2015). How is higher WNK1 activity maintained in immature neurons despite the higher intracellular chloride, which is inhibitory toward WNK1?…”
Section: Emerging Functions Of the Wnk Signaling Axis In Developmentmentioning
confidence: 86%
See 1 more Smart Citation
“…In this regards, recently, Friedel et al (15) showed that in immature neurons WNK1, SPAK, and KCC2 form a physical complex that triggers a shift in GABA activity (from excitatory to inhibitory) by promoting the dephosphorylation of two COOH-terminal threonines in KCC2 (T906 and T1007) and thus enhancing KCC2-mediated Cl Ϫ -extrusion. The authors suggest that WNK1 is a specific kinase that contributes to the developmental control of KCC2 activity and due to its relevance in several neurodevelopmental disorders such as neonatal seizures, autism among others, this interaction has an important neuropsychiatric value, since KCC2 activity is suppressed and GABAergic disinhibition promotes the hyperexcitability of neurons and circuits (15). We have recently report the case of a patient with an activating mutation of NKCC1 that is associated with the development of schizophrenia (41).…”
Section: Discussionmentioning
confidence: 99%